Revolusi Manajemen Dakwah: Integrasi Artificial Intelligence dalam Strategi Dakwah Kontemporer - Al Kahfi (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya, UIN Sunan Ampel Surabaya, 2025)
In the digital era, artificial intelligence (AI) plays an increasingly significant role in Islamic da'wah management. This research examines how AI can be integrated into contemporary da'wah strategies to increase the effectiveness of Islamic propagation. The main focus of the research includes Big Data analysis to understand religious trends, personalized da'wah content based on audience preferences, the development of an Islamic chatbot for more responsive interactions, and the automation of da'wah content distribution through digital media. The research method used is a literature review approach and a comparative analysis between conventional and AI-based da'wah methods. The results show that AI can increase the reach and efficiency of da'wah by providing a more interactive and relevant experience for the audience. However, AI implementation also faces challenges, such as algorithmic bias, limitations in understanding the spiritual and emotional aspects of da'wah, and the need for content validation to ensure it remains in line with Islamic principles. Furthermore, collaboration between religious scholars, academics, and technology practitioners is crucial to ensure that AI is used ethically and responsibly in da'wah. This study concludes that AI has great potential to support Islamic preaching in the digital era, but it must remain a tool that complements the role of ulama and da'i, not replace them. With wise integration and proper oversight, AI can be an innovative solution to strengthen da'wah that is more inclusive, adaptive, and relevant to current developments.